Security on a cryptographic model based on chaos - WEI Jun1; LIAO Xiao-feng2; YANG Ji-yun2 (Tongxin xuebao)
The application of chaos in cryptography has attracted much attention,however,most of them were cracked soon after publications.To find why they are so weak under the attack to their chaotic signal streams,some chaotic cryptosystems were investigated.A mathematical model was then derived from these cryptosystems.Attack and corre-sponding improvement were deployed based on the model.The research is validated with a cryptanalysis on a chaotic en-cryption scheme presented by LI S J in Physics Letters A.